(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The phenomenon of storytelling art of manaschi is revealed via the prism of archetypes theory by C.G. Yung. On the basis of the analysis we draw correlation of this phenomenon with myth-ritual practice and ancient archetypical layers of collective memory, the bearers of which are storytellers-manaschi. Key words: storytelling art of manaschi, archetypes, symbols, collective memory, unconscious collective, myth-ritual practice, dream.